Backbone boogie : dance the osteoporosis away! - Gey, Elainn Yee Rong (Nanyang Technological University, 2020)
This paper presents Backbone Boogie: Dance the Osteoporosis Away!, a health communications campaign seeking to promote the early prevention of osteoporosis through dance, initiated by three final-year students from Wee Kim Wee School of Communication and Information, Nanyang Technological University, Singapore. The campaign focuses on raising awareness of this health issue and encouraging the adoption of dance as a regular form of exercise among working women in Singapore aged 30 to 50. Based on the formative research gathered, reducing susceptibility to osteoporosis was found to be largely dependent on early prevention through a combination of calcium, vitamin D and regular weight-bearing exercise. Exercise was the least known aspect of osteoporosis prevention by the target audience and about 50% did not regularly exercise at all. Dance was also found to be the osteogenic exercise they were most keen to take up. Hence, campaign activities were to focus on increasing awareness of osteoporosis, the importance of exercise in osteoporosis prevention, and to introduce dance as an easy way to start exercising regularly. Offline outreach was unfortunately disrupted by the outbreak of COVID-19, necessitating a switch to a fully digital campaign. Combined with several other factors, the campaign unfortunately was not successful in meeting its objectives. An evaluation of the campaign’s effectiveness showed an increase in knowledge of osteoporosis and the need for early prevention. While post-campaign survey analysis found that more women exposed to the campaign have started dancing to prevent osteoporosis, awareness regarding the importance of dance in osteoporosis prevention was not proportionately increased.